Becoming "La Señorita de Inglés" in the U.S. Peace Corps: My Journey From Practitioner to Ph.D. - Nilofer K. Bharwani; Thomas J. Hodges (Journal of Community Engagement and Scholarship)
The Peace Corps is a governmental organization, founded in 1961 by President John F. Kennedy, with the objective of connecting United States citizens to the global community through service, community engagement, intercultural exchange, and collaboration. Peace Corps Volunteers (PCVs) serve in communities around the globe, promoting improved health, education, agriculture, and commerce. This essay provides a reflection on Peace Corps service and its impact on research.